2020
DOI: 10.1002/slct.202000934
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent pH‐Responsive Mesoporous Silica Nanoparticles with Core‐Shell Feature as a Traceable Delivery Carrier for Ibuprofen

Abstract: The fluorescent pH-responsive mesoporous silica nanoparticles (P@BMMs) were prepared, in which, the (2-[3-(triethoxysilyl) propyl]-1H-Benz [de]isoquinoline-1, 3(2H)-dione) -poly(acrylic acid) (PID-PAA) shell was covalently anchored onto the vinylmodified surface of the bimodal mesoporous materials (BMMs) core via one-step or two-step process. Their structural features were analyzed by XRD, SEM, TEM, TG, and SAXS, and the results showed that P@BMMs possessed typical fractal features from structural irregulari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Meanwhile, using vinyl-modified bimodal mesopores SiO 2 (abbreviated as BMMs) as a core and pH-sensitive fluorescent polymers as a shell, pH-responsive fluorescent hybrid nanoparticles (P@BMMs) with core-shell structures were successfully prepared. The results revealed that the fluorescence intensity of the resultant P@BMMs nanoparticles could achieve a good fluorescence labeling effect for potential application in tracing drug sustained/controlled delivery fields [ 16 ]. However, the fluorescent performances are uncertain in the drug delivery process due to unclear understanding of the dispersion behaviors and agglomeration properties of organic fluorescent molecules in the drug carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, using vinyl-modified bimodal mesopores SiO 2 (abbreviated as BMMs) as a core and pH-sensitive fluorescent polymers as a shell, pH-responsive fluorescent hybrid nanoparticles (P@BMMs) with core-shell structures were successfully prepared. The results revealed that the fluorescence intensity of the resultant P@BMMs nanoparticles could achieve a good fluorescence labeling effect for potential application in tracing drug sustained/controlled delivery fields [ 16 ]. However, the fluorescent performances are uncertain in the drug delivery process due to unclear understanding of the dispersion behaviors and agglomeration properties of organic fluorescent molecules in the drug carrier.…”
Section: Introductionmentioning
confidence: 99%
“…In our preliminary work [ 25 , 26 , 27 ], a series of luminescent hybrid nanoparticles with effectively luminescent performances was prepared using BMMs as a carrier and NA derivatives as luminescent probes through surface modification, presenting a longer fluorescent lifetime (2.2–3.4 ns) that was caused by the delocalized pair of electrons in the electron-withdrawing conjugate structures. Thereafter, Liu et al and Wei et al [ 28 , 29 ] further developed a series of core–shell structured nanocomposites with strong fluorescent features and dual temperature- and pH-responsive properties through self-assembly technology, in which the BMM was used as a core and the fluorescent molecule PID-dispersed P(NIPAM-co-AA) acted as a shell. Notably, the resultant hybrid nanocomposite PID/P@BMMs with two lifetimes of 2.53 and 18.86 ns not only possessed an excellent controlled IBU release of 71.1% at 37 °C and 82.7% at pH 2.0 but also presented a stable fluorescence intensity at the 395–450 nm wavelength during drug loading and releasing.…”
Section: Introductionmentioning
confidence: 99%